AGC705: Microbiol Control Issues / Faculty of Plantation and Agrotechnology - UiTM, Faculty of Plantation and Agrotechnology (Universiti Teknologi MARA (UiTM), 2018)
This course covers the biological fundamentals of microbes, its impact to the plant and efforts to prevent and limit their spread. Besides that, it also will discuss issues as they relate to the environmental science and sustainable agriculture. Students are expected to actively participate in the discussion, and find, present and critique recent literature in the field of microbial control issues.